Oncologic palliative care: perception of family health strategy teams (Research, Society and Development, 2020)
This study aimed to identify the perception of professionals in the Family Health Strategy about palliative oncology care in Primary Health Care. Fifteen professionals from the Family Health Strategy teams of a basic health unit in a municipality participated in the study, medium-sized in Santa Catarina (Brazil), which provided care to cancer patients in palliative care in the territory covered. The data collected from semi-structured individual interviews and analyzed through content analysis resulted in three final categories: Understanding Palliative Care; Interprofessional Performance; Emotional Aspects of Caring. Although palliative care is part of the care for cancer patients, this approach is not yet fully understood, restricting the care process to the relief of physical symptoms and support for specific needs. However, it is worth noting that professionals show care for the feelings that patients and family members experience when faced with the progression of the disease to the end of life process. In an attempt to alleviate such fragility, professionals point to Psychology as a valid resource that will help the patient and his family in the elaboration of the sufferings that they experience during the illness.